Liver-on-a-Chip‒Magnetic nanoparticle bound synthetic metalloporphyrin-catalyzed biomimetic oxidation of a drug in a magnechip reactor - Decsi Balázs; Krammer Réka; Hegedűs Kristóf; Ender Ferenc; Gyarmati Benjámin Sándor; Szilágyi András Ferenc; Tőtős Róbert; Katona Gabriel; Paizs Csaba; Balogh György Tibor; Poppe László; Balogh Weiser Diána (2019)
Biomimetic oxidation of drugs catalyzed by metalloporphyrins can be a novel and promising way for the effective and sustainable synthesis of drug metabolites. The immobilization of 5,10,15,20-tetrakis(2,3,4,5,6-pentafluorophenyl)iron(II) porphyrin (FeTPFP) and 5,10,15,20‐tetrakis‐(4‐sulfonatophenyl)iron(II) porphyrin (FeTSPP) via stable covalent or rapid ionic binding on aminopropyl-functionalized magnetic nanoparticles (MNPs-NH2) were developed. These immobilized catalysts could be efficiently applied for the synthesis of new pharmaceutically active derivatives and liver related phase I oxidative major metabolite of an antiarrhythmic drug, amiodarone integrated in a continuous-flow magnetic chip reactor (Magnechip).